WORKSHOP KOMUNIKASI KESEHATAN LINGKUNGAN BAGI MASYARAKAT DESA DI WILAYAH BANDUNG BARAT - Sjoraida, Diah Fatma; Bakti, Iriana; Nugraha, Aat Ruchiat (Ekalaya: Jurnal Pengabdian Kepada Masyarakat Indonesia, 2023)
The workshop that raised the issue of "One Waste a Thousand Disasters" became an important thing for the people of Mekarmukti Village, Cihampelas District, West Bandung Regency in an effort to eliminate environmental pollution around the Citarum river basin. The purpose of the workshop in the Community Service (PKM) program is to find out and practice household and small business waste management through the liquid fertilizer-based waste treatment tool "ROSDA" and the fish farming tool "BUDIKDADRUM" which can produce selling value that is delivered communicatively and interactively. The result of this wokrshop program is an increase in community knowledge and skills about the economic value of household and small business waste in the Mekarmukti Village environment as well as increasing public interest in trying to process tofu, tempeh and pindang fish product waste independently